(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
In the 1960s, the process of agricultural land development began to be actively implemented in Andizhan region. The main goal of this process was to effectively organize agricultural production by increasing land fertility, improving land reclamation and irrigation systems. On most of the developed lands, appropriate infrastructure was created to increase land fertility, including the creation of new arable land. As a result, a significant increase in productivity was achieved